The effect of biopesticide and combined fertilization in promoting plant health and growth of tomato cultivated on peat soil in West Kalimantan - Dwi Purnamawati Widiastuti; Abdullah Umar (Universitas Lampung, 2022)
The demand for horticultural products that are cultivated organically has increased. However, the susceptibility of plants to pests and diseases becomes an obstacle in organic crop cultivation. The use of biopesticides can be a solution to overcome these problems with the added benefit due to its environmental friendly and sustainable aspect. The purpose of this study was to determine the effect of biopesticides and combined fertilization in promoting plant health and enhancing tomato growth on the peat soil. This study used a randomized complete block design with two factors and three replications. The first factors were four combined fertilizations (K), namely: K1: 100% organic fertilizer+local microorganisms; K2: 75% inorganic fertilizer+Petrobio, K3: 75% inorganic fertilizer+M-Dec, and K4: 100% inorganic fertilizer. The second factors were three types of pesticides (S), namely: S1: homemade biopesticides, S2: industrial biopesticides containing active ingredient Eugenol 188,4 g L-1, and S3: chemical pesticides containing active ingredient fipronil 50 g L-1. The observed data were analyzed statistically using Analysis of Variance (ANOVA) and further tests were carried out using Duncan’s Multiple Range Test (DMRT) at the 5% level. The results showed that the tuba roots and betel leaves used in biopesticides had different effects on controlling fruit flies and leafminer caterpillars, as well as anthracnose disease. The application of chemical pesticides influenced the lowest infestation of fruit flies and leafminer caterpillars, while homemade and industrial biopesticides, as well as chemical pesticides had the same effect in reducing the intensity of anthracnose. In conclusion, a combination of 100% inorganic fertilizer+industrial biopesticides and 75% inorganic fertilizer+Petrobio gave greater tomato yields. Biopesticides could sustain organic crop cultivation in peatlands considering the ingredients availability, affordable, and easy application.